L’honneur d’un fils de disparu - Lætitia Bucaille (Criminocorpus)
The experience of the son of an Algerian nationalist militant tortured and liquidated by the French army during the War of Independence, denied access, like so many others, to truth and justice, is put into perspective with the government's management of the memory of the War of Liberation. The individual and official registers of homage to the heroes who died for the nation largely converge; yet they are also in tension insofar as the FLN promotes a unanimist and simplifying narrative about the past that obliterates the complexity and contradictions of Algerian society. The martyr's son intends not only to honor his father and obtain precise information on the circumstances of his death, but also to restore his family's honor.